Uncertainty about future income: Initial beliefs and resolution during college - Yifan Gong; Todd R. Stinebrickner; Ralph Stinebrickner (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2018)
Uncertainty about future income plays a conceptually important role in college decisions. Unfortunately, characterizing how much earnings uncertainty is present for students at college entrance and how quickly this uncertainty is resolved has proven to be difficult. This paper takes advantage of unique expectations data from the Berea Panel Study to provide new evidence about this issue. We characterize initial uncertainty using survey questions that elicit the entire distribution describing one's beliefs about future earnings at an ideal time - immediately before students began their first year courses. We characterize the amount of uncertainty that is resolved during college by taking advantage of the longitudinal nature of the expectations data. Taking advantage of a variety of additional survey questions, we provide evidence about how the resolution of income uncertainty is influenced by factors such as college GPA and college major, and also examine why much income uncertainty remains unresolved at the end of college.
Keywords: 330